OPTIMALISASI ALUR DISTRIBUSI: MEMPERLANCAR EFISIENSI MELALUI DAFTAR HARGA PENGIRIMAN DAN MODA TRANSPORTASI YANG STRATEGIS - Muhamad Galih, Saddam Alwan; Sukmadewi, Rani (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
PT XY, as a digital-based logistics company with integrated solutions, is striving to enhance the efficiency of its distribution workflow in the face of increasingly complex global business dynamics. Confronting a competitive market, PT XY considers the compilation of a shipping and truck pricing list as an essential foundation to improve competitiveness, expand market share, and build a reputation in the ever-changing market. This approach is not merely a pricing strategy but a necessity to remain relevant and effectively meet customer needs in a dynamic business era. The chosen strategy involves collaboration with external parties, especially logistics transportation vendors, to formulate effective pricing tariffs and select the appropriate mode of transportation. The process of tariff formation includes an analysis of destination routes, carried loads, and transportation modes, with a focus on logistics efficiency and the needs of the Indonesian market. This research is conducted using a qualitative method with the aim of finding solutions to the challenges faced by PT XY.